2008
DOI: 10.1080/01443610802042589
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of domestic violence in antenatal attendee's in a Delhi hospital

Abstract: The objective of the study was to determine the prevalence of domestic violence (DV) in women attending an antenatal clinic in a Delhi hospital; to investigate any associated risk factors; main perpetrators; forms and severity of violence. An anonymous validated questionnaire was used. A total of 26.9% of women reported physical abuse. Emotional and sexual abuse was reported by 29% and 6.2%, respectively. The prevalence of DV was similar in women from different religions or age groups. The prevalence was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Comparable to our findings, most of the violence was perpetrated by a woman’s husband in many studies conducted in different parts of the world. Other perpetrators such as the mother-in-law, father-in-law, and sister-in-law committed very few DV towards women during pregnancy [20, 23, 25, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Comparable to our findings, most of the violence was perpetrated by a woman’s husband in many studies conducted in different parts of the world. Other perpetrators such as the mother-in-law, father-in-law, and sister-in-law committed very few DV towards women during pregnancy [20, 23, 25, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Spouse was the perpetrator in 47.4% cases and other family members were responsible for 31% events. About 89% women reported they had no control over their lives and major family decisions (Singh et al 2008). In Wardha, Maharashtra, about 97% of pregnant women ( n ϭ 2000) reported that they had sexual intercourse with their partners during the current pregnancy; however, 30.7% women said that they had been forced to do so against their wishes.…”
Section: Prevalence and Nature Of Violencementioning
confidence: 99%
“…IPV has been described as more likely to be experienced by women from lower castes [43], larger families, and certain faith groups [7,11,18,49]. There is some evidence that women who have witnessed abuse in their families are more likely to experience it themselves [10,45]. …”
Section: Introductionmentioning
confidence: 99%
“…Longer marriages may be associated with increased [15] or decreased risk [7]. As with their partners, women with less education are at greater risk of IPV [7,11,13,18,27,45-47,50,54]. It has been suggested that women who are more educated than their husbands are at greater risk [50], but this has not been substantiated and a recent study found the opposite [58].…”
Section: Introductionmentioning
confidence: 99%